Alkaline-surfactant-polymer flooding of active oil under reservoir conditions. (15th February 2020) - Sui, Xin; Chen, Zhao; Kurnia, Ivan; Han, Xu; Yu, Jianjia; Zhang, Guoyin
Abstract: In this study, we conducted an alkaline/surfactant/polymer (ASP) coreflood at real reservoir temperature and pressure using reservoir core plugs and active live oil. The live oil was prepared by dissolving gases (CH4 and CO2 ) into dead crude with acid number of 1 mg KOH/g oil and their miscibility under reservoir conditions (62 °C and 1700 psig) was tested in a sapphire PVT cell. The results verified the oil and gases were able to reach one single phase after contact time close to 9 hours, which meant no phase separation would occur during live oil coreflood as long as pore pressure was maintained above 1700 psig. After the miscibility test, live oil coreflood was carried out in porous media made of a 1-ft long reservoir core stack. This stack was first restored to the natural reduced reservoir environment following a thorough cleaning. Surfactant formulation screened based on phase behavior tests with dead crude showed remarkable aqueous solubility and interfacial tension reduction capability (solubilization ratio around 60 cc/cc). As low as 0.3% surfactant concentration was used in this coreflood. The injection of 0.3 PV ASP and 3.15 PV polymer recovered 44.5% original oil in place over waterflooding, which accounted for over 90% waterflooding residual oil. The analysis indicated ASP slug was injected at overoptimum salinity (live oil supposed to have a decreased optimum salinity compared to dead crude), which partially fitted the concept of negative salinity gradient that played a positive influence on oil displacement.